DETERMINATION OF MICROHARDNESS AND DEPTH OF THERMALLY HARDENING ZONE IN QUALITY CARBON STRUCTURAL STEEL AFTER WEDM USING DIFFERENT DISCHARGE PARAMETERS (Nonconventional Technologies Review, 2020)
This article presents experimental studies of microhardness distributions along the depth of the thermally hardened zone in high-quality carbon Steel 45 (analog DIN 1.0503) after wire electrical discharge machining (WEDM) using а wide range of modes with known energy and time parameters of a single spark discharge. In the zone of thermal hardening of Steel 45 after WEDM were revealed extreme values of microhardness which exceed the maximum achievable at standard hardening of this grade of steel. In areas of ultrahigh hardness microcracks are absent. It is established that in WEDM of high-quality carbon steels with the use of discharge current pulses with energy and time parameters characteristic of modern EDM cutting machines, the current pulse duration has a dominant influence on the formation of the thickness of the thermally hardened layer. The amount of discharge energy released at the anode, within the parameters of the experiments, has a secondary effect on the machining process. The possibility of effectively influencing the formation of the necessary physical and mechanical properties of the surface layers of carbon steel parts with the help of time parameters of a single spark discharge is proved. It is proposed to use the obtained results to predict the thickness of the thermally hardened layer at WEDM of a wide group of structural and tool carbon steels. The established regularities expand the idea of the mechanisms of influence of time-energy characteristics of spark discharges on the formation of thermally hardened layer at WEDM of high-quality carbon steels and correlate well with the known research results in the field of electrophysical methods of materials machining.
Keywords: wire electrical discharge machining; thermally hardened zone; microhardness; heat-affected zone